Host erythrocyte polymorphisms and exposure to Plasmodium falciparum in Papua New Guinea. - Fowkes, F; Michon, P; Pilling, L; Ripley, R; Tavul, L; Imrie, H; Woods, C; Mgone, C; Luty, A; Day, K (BioMed Central, 2008)
BACKGROUND: The protection afforded by human erythrocyte polymorphisms against the malaria parasite, Plasmodium falciparum, has been proposed to be due to reduced ability of the parasite to invade or develop in erythrocytes. If this were the case, variable levels of parasitaemia and rates of seroconversion to infected-erythrocyte variant surface antigens (VSA) should be seen in different host genotypes. METHODS: To test this hypothesis, P. falciparum parasitaemia and anti-VSA antibody levels were measured in a cohort of 555 asymptomatic children from an area of intense malaria transmission in Papua New Guinea. Linear mixed models were used to investigate the effect of alpha+-thalassaemia, complement receptor-1 and south-east Asian ovalocytosis, as well as glucose-6-phosphate dehydrogenase deficiency and ABO blood group on parasitaemia and age-specific seroconversion to VSA. RESULTS: No host polymorphism showed a significant association with both parasite prevalence/density and age-specific seroconversion to VSA. CONCLUSION: Host erythrocyte polymorphisms commonly found in Papua New Guinea do not effect exposure to blood stage P. falciparum infection. This contrasts with data for sickle cell trait and highlights that the above-mentioned polymorphisms may confer protection against malaria via distinct mechanisms.